Characterization and complete genome sequence of highly lytic phage active against methicillin-resistant Staphylococcus aureus (MRSA) isolated from Egypt - Abeer K. Abd El-Tawab; B. A. Othman; A. Sharaf; Samar S. El-Masry; T.F. El-Arabi (Virology Journal)
Abstract Background Methicillin-Resistant Staphylococcus aureus (MRSA) is one of the most resistant bacteria to antibiotics. S. aureus is an important, widespread pathogen that can cause a variety of infectious diseases in humans and animals. Phages have been recognized as natural, safe, highly specific and effective alternatives agents to antibiotics for preventing and treating bacterial infections caused by MRSA. Therefore, this study aims at the characterization of a novel isolated lytic phage, vB_SauP_ASUmrsa123. Methods Isolates of Staphylococcus aureus MRSA were obtained on Mannitol Salt Agar and Baird Parker Agar plates and confirmed using VITEK 2. Sewage and clinical samples were used to isolate specific phages for S. aureus MRSA, and plaque assays were used for host range determination on Luria-Bertani (LB) media. The phage morphology of the isolated phage was determined by transmission electron microscopy. The phage’s whole genome sequencing was identified. Results A total of 25 isolates of Staphylococci were obtained from different clinical sources and showed typical colonies on Baird-Parker and Mannitol Salt Agar plates. The VITEK 2 automated system revealed that all 25 isolates were confirmed as S. aureus (MRSA). Two of the most antibiotics-resistant isolates were further confirmed using 16S ribosomal RNA sequencing. A lytic phage was detected against the MRSA isolates tested In Vitro, namely vB_SauP_ASUmrsa123. The phage belonged to Rountreeviridae family based on morphological properties observed by TEM and the host range of the isolated phage was tested on the 25 clinical MRSA isolates in Vitro. The one-step growth curve of the isolated phage showed that the latent period was about 55 min, and the burst size was estimated at 167 PFU. The whole genome sequencing and annotation of genes revealed that phage vB_SauP_ASUmrsa123 contained a linear dsDNA with a size of about 17,155 bp with predicted 24 ORFs. Analysis of its genome provides valuable information approximately the variety of phages belonging to the staphylococcal phages class I. Conclusion A lytic Podo Phage vB_SauP_ASUmrsa123 was identified against S. aureus MRSA isolates and its genome was sequenced. The phage was found to be eligible for potential application in biocontrol.